The impact of remittances on economic growth: An econometric model - Dietmar Meyer; Adela Shera (EconomiA, 2017)
Remittances in the world represent one of major international financial resources, which sometimes they exceed the flows of foreign direct investment (FDI). For centuries, there have been heated debates on the sources of economic growth in developing economies and also why some countries reflect strong economic growth comparing to others. This study aims to observe the impacts of remittances on economic growth, using panel data set of six high remittances receiving countries, Albania, Bulgaria, Macedonia, Moldova, Romania and Bosnia Herzegovina during the period 1999–2013. These countries have experienced a major increase in remittance inflows, and at this time accounts for the bulk of total remittance receipts, compared with other regions. Most countries, remittances represent the largest source of foreign exchange earnings and represent more than 10 percent of GDP. In other words, the econometric analysis will be based on those six remittance receiving countries. The paper is then to review the empirical literature devoted to the impact of remittances on economic growth, in order, to identify empirically if there are significant relationships between remittances and growth in these countries. The results suggest that remittances have a positive impact on growth and that this impact increases at higher levels of remittances relative to GDP. – – As remessas no mundo representam um dos principais recursos financeiros internacionais, que por vezes ultrapassam os fluxos de investimento diretto estrangeiro (IDE). Durante séculos, tem havido acalorados debates sobre as fontes de crescimento econômico em economias em desenvolvimento e também porque alguns países refletem forte crescimento econômico em comparaç\~ao com outros. Este estudo tem como objetivo observar os impactos das remessas sobre o crescimento econômico, usando o conjunto de dados de seis países receptores de remessas, a Albânia, a Bulgária, a Macedônia, a Moldávia, a Romênia e a Bósnia-Herzegovina durante o período 1999-2013. Esses países experimentaram um grande aumento nos fluxos de remessas e, neste momento, respondem pela maior parte das receitas totais de remessas, em comparaç\~ao com outras regi\~oes. Na maioria dos países, as remessas representam a maior fonte de divisas que correspondem a mais de 10% do PIB. A análise econométrica será baseada nos seis países receptores de remessas. O trabalho objetiva rever a literatura empírica dedicada ao impacto das remessas sobre o crescimento econômico, a fim de identificar empiricamente se há relaç\~oes significativas entre remessas e crescimento nesses países receptores de remessas. Os resultados sugerem que as remessas têm um impacto positivo no crescimento e que esse impacto aumenta com o nível de remessas em relaç\~ao ao PIB."
Keywords: 330; Remittances; Economic growth; Panel data; Remessas; Crescimento econômico; Análise de dados de painel